Elimination of carbon catabolite repression in Clostridium tyrobutyricum for enhanced butyric acid production from lignocellulosic hydrolysates. (August 2022) - Fu, Hongxin; Zhang, Huihui; Guo, Xiaolong; Yang, Lu; Wang, Jufang
Graphical abstract: Highlights: Xylose pathway genes in C. tyrobutyricum were identified and verified. The potential mechanisms of CCR in C. tyrobutyricum were proposed and confirmed. Double knockout of hprK and xylR eliminated CCR in C. tyrobutyricum. Undetoxified lignocellulosic hydrolysates were used as the substrates. Abstract: Clostridium tyrobutyricum, a gram-positive anaerobic bacterium, is recognized as the promising butyric acid producer. But, the existence of carbon catabolite repression (CCR) is the major drawback for C. tyrobutyricum to efficiently use the lignocellulosic biomass. In this study, the xylose pathway genes were first identified and verified. Then, the potential regulatory mechanisms of CCR in C. tyrobutyricum were proposed and the predicted engineering targets were experimental validated. Inactivation of hprK blocked the CcpA-mediated CCR and resulted in simultaneous conversion of glucose and xylose, although xylose consumption was severe lagging behind. Deletion of xylR further shortened the lag phase of xylose utilization. When hprK and xylR were inactivated together, the CCR in C. tyrobutyricum was completely eliminated. Consequently, ATCC 25755/Δ hprK Δ xylR showed significant increase in butyrate productivity (1.8 times faster than the control) and excellent butyric acid fermentation performance using both mixed sugars (11.0–11.9 g/L) and undetoxified lignocellulosic hydrolysates (12.4–13.4 g/L).